Free heme exacerbates colonic injury induced by anti-cancer therapy - Seika, Philippa; Janikova, Monika; Asokan, Sahana; Janovicova, Lubica; Csizmadia, Eva; O’Connell, Mckenzie; Robson, Simon C.; Glickman, Jonathan; Wegiel, Barbara (Frontiers in Immunology, 2023)
Gastrointestinal inflammation and bleeding are commonly induced by cancer radiotherapy and chemotherapy but mechanisms are unclear. We demonstrated an increased number of infiltrating heme oxygenase-1 positive (HO-1+) macrophages (Mø, CD68+) and the levels of hemopexin (Hx) in human colonic biopsies from patients treated with radiation or chemoradiation versus non-irradiated controls or in the ischemic intestine compared to matched normal tissues. The presence of rectal bleeding in these patients was also correlated with higher HO-1+ cell infiltration. To functionally assess the role of free heme released in the gut, we employed myeloid-specific HO-1 knockout (LysM-Cre : Hmox1flfl), hemopexin knockout (Hx-/-) and control mice. Using LysM-Cre : Hmox1flfl conditional knockout (KO) mice, we showed that a deficiency of HO-1 in myeloid cells led to high levels of DNA damage and proliferation in colonic epithelial cells in response to phenylhydrazine (PHZ)-induced hemolysis. We found higher levels of free heme in plasma, epithelial DNA damage, inflammation, and low epithelial cell proliferation in Hx-/- mice after PHZ treatment compared to wild-type mice. Colonic damage was partially attenuated by recombinant Hx administration. Deficiency in Hx or Hmox1 did not alter the response to doxorubicin. Interestingly, the lack of Hx augmented abdominal radiation-mediated hemolysis and DNA damage in the colon. Mechanistically, we found an altered growth of human colonic epithelial cells (HCoEpiC) treated with heme, corresponding to an increase in Hmox1 mRNA levels and heme:G-quadruplex complexes-regulated genes such as c-MYC, CCNF, and HDAC6. Heme-treated HCoEpiC cells exhibited growth advantage in the absence or presence of doxorubicin, in contrast to poor survival of heme-stimulated RAW247.6 Mø. In summary, our data indicate that accumulation of heme in the colon following hemolysis and/or exposure to genotoxic stress amplifies DNA damage, abnormal proliferation of epithelial cells, and inflammation as a potential etiology for gastrointestinal syndrome (GIS).